Mutations of the phenylalanine hydroxylase gene in Iranian patients with phenylketonuria - Biglari, Alireza (Springerplus, 2015)
Phenylketonuria (PKU) is an autosomal recessive disease which results from mutations in the phenylalanine hydroxylase (PAH) gene. The aim of this study was the identification of sixteen different mutations in Iranian patients with hyperphenylalaninemia. The mutations were detected during the characterization of PAH genotypes of 39 PKU patients from Qazvin and Zanjan provinces of Iran. PAH mutations have been analyzed by PCR and direct sequencing of PCR products of the promoter region and all 13 exons of PAH gene, including the splicing sites. A mutation detection rate of 74.3 % was realized. Two mutations were found at high frequencies: R176X (10.25 %) and p.P281L (10.25 %). The frequencies of the other mutations were: IVS2+5G>A (2.56 %), IVS2+5G>C (2.56 %), p.L48S (2.56 %), p.R243Q (2.56 %), p.R252Q (5.12 %), p.R261Q (7.69 %), p.R261X (5.12 %), p.E280K (2.56 %), p.I283N (2.56 %), IVS9+5G>A (2.56 %), IVS9+1G>A (1.28 %), IVS11+1G>C (1.28 %), p.C357R (1.28 %), c.632delC (2.56 %). The present results confirm the high heterogeneity of the PAH locus and contribute to information about the distribution and frequency of PKU mutations in the Iranian population.